2008
DOI: 10.1002/cncr.23774
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of dedifferentiation in retroperitoneal liposarcoma

Abstract: BACKGROUND.A series of patients with well differentiated (WD)/dedifferentiated (DD) retroperitoneal liposarcoma (RLS) was studied to evaluate the prognostic value of the presence, extension, and grade of the DD component.METHODS.Among 148 patients with RLS who underwent surgery over 20 years, the authors retrieved data on patients who had localized WD/DD RLS. For the current analysis, patients were included only if they had primary disease or a first recurrence at their initial presentation. The DD component, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 32 publications
2
53
1
Order By: Relevance
“…Liposarcoma is the second most common STS and has different subtypes: well-differentiated/dedifferentiated; mixoid/round cell and pleomorphic 4 5–7. RLSs account for 0.1% of all malignancies and the majority of them tend to be well differentiated and dedifferentiated 2 4–5 16.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Liposarcoma is the second most common STS and has different subtypes: well-differentiated/dedifferentiated; mixoid/round cell and pleomorphic 4 5–7. RLSs account for 0.1% of all malignancies and the majority of them tend to be well differentiated and dedifferentiated 2 4–5 16.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that RLS have a higher rate of local recurrence (43%) compared to liposarcomas arising from the trunk or extremities (10–16%) 2 7. The histological type also plays an important role in prognosis 4 16. Dedifferentiated RLS have a high incidence of local recurrence (83%), distant metastasis (30%) and a decreased 5-year overall survival (20%) than those with well-differentiated subtype, according to the MSKCC series 7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gastrointestinal stromal tumours are not included in RPS as they arise from the gut. Well differentiated sarcomas may convert to de-differentiated sarcomas after one or more recurrences [16,17]. Well differentiated sarcomas have better outcomes in terms of recurrence, rate of metastasis and overall survival compared to de-differentiated sarcomas.…”
Section: Pathologymentioning
confidence: 99%